Effect of DSS-Induced Ulcerative Colitis and Butyrate on the Cytochrome P450 2A5: Contribution of the Microbiome - Satka, Stefan; Frybortova, Veronika; Zapletalova, Iveta; Anzenbacher, Pavel; Anzenbacherova, Eva; Kozakova, Hana; Srutkova, Dagmar; Hudcovic, Tomas; Jourova, Lenka (International journal of molecular sciences, 2022)
Several studies have indicated the beneficial anti-inflammatory effect of butyrate in inflammatory bowel disease (IBD) therapy implying attempts to increase butyrate production in the gut through orally administered dietary supplementation. Through the gut-liver axis, however, butyrate may reach directly the liver and influence the drug-metabolizing ability of hepatic enzymes, and, indirectly, also the outcome of applied pharmacotherapy. The focus of our study was on the liver microsomal cytochrome P450 (CYP) 2A5, which is a mouse orthologue of human CYP2A6 responsible for metabolism of metronidazole, an antibiotic used to treat IBD. Our findings revealed that specific pathogen-free (SPF) and germ-free (GF) mice with dextran sulfate sodium (DSS)-induced colitis varied markedly in enzyme activity of CYP2A and responded differently to butyrate pre-treatment. A significant decrease (to 50%) of the CYP2A activity was observed in SPF mice with colitis; however, an administration of butyrate prior to DSS reversed this inhibition effect. This phenomenon was not observed in GF mice. The results highlight an important role of gut microbiota in the regulation of CYP2A under inflammatory conditions. Due to the role of CYP2A in metronidazole metabolism, this phenomenon may have an impact on the IBD therapy. Butyrate administration, hence, brings promising therapeutic potential for improving symptoms of gut inflammation; however, possible interactions with drug metabolism need to be further studied.
Keywords: cytochromes P450; gut inflammation; modely nemocí na zvířatech; Dextran Sulfate; střevní mikroflóra; gut–liver axis; microbiome; ulcerózní kolitida; systém (enzymů) cytochromů P-450; Metronidazole; Anti-Inflammatory Agents; Mice; zvířata; antibakteriální látky; Gastrointestinal Microbiome; Disease Models, Animal; Colitis, Ulcerative; antiflogistika; butyrate; síran dextranu; hepatic drug metabolism; myši; metronidazol; Animals; Anti-Bacterial Agents; Butyrates; Mice, Inbred C57BL; Cytochrome P-450 Enzyme System; germ-free mice; myši inbrední C57BL; butyráty